Pengaruh Literasi Keuangan, Inklusi Keuangan, Aplikasi Keuangan Digital, Pendapatan dan Gaya Hidup terhadap Perilaku Menabung Generasi Z di Purwokerto - Marlia Neni Nadiati; Dian Safitri Pantja Koesoemasari; Nirmala Nirmala (ProBisnis : Jurnal Manajemen, 2026)
This study aims to analyze the influence of financial literacy, financial inclusion, digital financial applications, income, and lifestyle on the saving behavior of Generation Z in Purwokerto. Saving behavior among the younger generation has shifted significantly, driven by rapid technological advancements and the emergence of digital financial platforms that simplify access to savings and investment instruments. Employing a quantitative approach, this research utilized a survey method with questionnaires distributed to 100 respondents selected via accidental sampling. Data were analyzed using multiple linear regression. The results indicate that financial literacy, financial inclusion, digital financial applications, and income have a positive and significant impact on saving behavior. Conversely, a consumptive lifestyle was found to have a negative and significant effect. These findings suggest that enhancing financial knowledge, expanding inclusion, and leveraging digital tools are essential for improving the saving habits of Generation Z, while a high level of consumerism remains a primary barrier to financial discipline.